g(x)=6x+2

Simple and best practice solution for g(x)=6x+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for g(x)=6x+2 equation:


Simplifying
g(x) = 6x + 2

Multiply g * x
gx = 6x + 2

Reorder the terms:
gx = 2 + 6x

Solving
gx = 2 + 6x

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Divide each side by 'x'.
g = 2x-1 + 6

Simplifying
g = 2x-1 + 6

Reorder the terms:
g = 6 + 2x-1

See similar equations:

| -4v-11=-v+7 | | -3y+6=3(2y+1)-1(4y-2) | | -4.52=3.2x+1.48 | | -12z-36=-10z+8 | | -5(3y-7)-y=-3(y-3) | | 7y-22=3y+2 | | 4x^2+y^2+4z^2-4y-24z+36=0 | | 3b^3-6b^2+3b=0 | | abs(3x+4)=14 | | -5x-10=2x-52 | | (22.50-x)-3.10=0 | | 7x+2+5x=38 | | 29=2x+3x-6 | | 9-7x+6x=-3 | | z^3+49z=0 | | 4y-6=4+6y | | 168=h+45h | | X+2ln(x)=0 | | 8x^4-3x^2-18=0 | | g=C*f | | 6x+8=5x-3 | | -4*2-6*2= | | -28=x-2x-7 | | 23/5+87/14= | | 14.4-5=9 | | 10.2-7.3x=-58 | | 13.95-5=9 | | 7y+2(y-5)=5(y+2)-5 | | 3w^2-23w-13=0 | | 5(2q)+(q-4)+q=5 | | 9x+5y+0.1z=100 | | 2(6)(h)+2(h)(17)+2(6)(17)=342 |

Equations solver categories